Ingenious appointment system / Muhammad Akmal Zakaria and Meor Muhammad Shazwan Shafiee - Zakaria, Muhammad Akmal; Shafiee, Meor Muhammad Shazwan (2015)
The focus of this project is for students to book appointments with their lecturers. Most of the current apps nowadays requires data plan to which some student do not have sufficient budget to access on their phones and in some cases the students themselves may not even have a smart phone. This smart appointment system tool is both hardware and software integrated into a device which will be an alternative for students who cannot contact their lecturers through mobile data communication. The main focus is on the problems faced by students and lecturers to meet and have appointments on certain days. Whenever the students went to the lecturer's office and do not manage to meet up with the lecturer, they can book appointments through the Ingenious Appointment System by entering their student ID and the desired appointment time. A GPS system is used by the device/hardware to send a notification to the lecturer's mobile phone whenever an appointment has been booked by the students. The lecturer in tum can set up to 3 choices of available time for the appointment. The system is limited to daily appointment booking so that all the schedules are updated. A buzzer is added to the device to identify any error entered by the user. An LED indicator is also added to the device which the lecturer can set manually to indicate whether they are in the campus, either out of the office or in the office.